Peranan Desa Wisata Dalam Pembangunan Desa Di Desa Munduk Kecamatan Banjar Kabupaten Buleleng - I Wayan Majuarsa; Ni Wayan Sutiani (Universitas Mahendradatta Denpasar, 2018)
Buleleng Regency is one of eight regencies in Bali that is known by foreign tourists as an attractive tourist destination, where the area has a variety of arts, culture and natural tour- ist attractions. Munduk Village has a variety of tourist attractions consisting of arts or culture and natural scenery, in the form of hills, rice fields, and waterfalls that are characteristic of the village. The concept of Tri Hita Karana is the basis for living the daily lives of local people in Munduk Village. Village tourism is a form of integration between attractions, accommodation and supporting facilities that are presented in a structure of community life that integrates with the prevailing procedures and traditions where tourists can stay in or close to the village to learn and enjoy life in the village.From the description of the background above, the formulation of the problem in this paper is: what is the role of tourism villages in the development of villages in Munduk Village, Banjar District, Buleleng Regency. The research method is done using interviews.Conclusions from the results of the study indicate that the role of the tourist village munduk in Munduk Village, Banjar Subdistrict, Buleleng Regency is as a source of income for the people in Munduk Village other than as farmers, considering the Munduk village area as a tourist vil- lage that is visited by many tourists which in turn can increase the income of the surrounding community. The suggestions that can be asked are: For the Munduk village government should be able to support tourism villages in Munduk by helping to provide funding facilities for devel- opment in order to develop. In addition, the community is given facilities for capital in order to build a business to support tourist villages in the village of Munduk, Banjar District, Buleleng Regency.